Social networks and social support of older immigrants in Aotearoa New Zealand - Szabó Á; Stephens C; Alpass F (Cambridge University Press, 2024)
Immigrants commonly report difficulties with developing social connections post-transition, which can lead to social isolation as they age. Understanding what factors promote/hinder the social integration of immigrants is an important public health objective. We tested the public health model of social integration of Berkman et al. in a sample of older immigrants. This model calls for considering both the social conditions in which social networks are embedded (upstream influences) and the levels of social support offered by different types of networks (downstream influences). First, we derived an empirical typology of social networks of older immigrants. Next, we tested associations of social networks with upstream and downstream influences. Data came from the New Zealand Health, Work and Retirement Study. The sample included 568 older adults (54% male) who immigrated as adults (mean length of stay = 28.5 years, standard deviation = 12.5). Latent profile analysis was employed on responses to the Practitioner Assessment of Network Type to identify social networks. Associations with upstream and downstream correlates were tested using logistic and multiple regression. Four network configurations emerged: ‘private-restricted’ (43.4%), ‘family-dependent’ (35.8%), ‘locally integrated’ (10.9%) and ‘wider community-based’ (9%). Having shorter length of residence and individualistic cultural background was predictive of being in a restricted network (private-restricted, family-dependent). Being in a restricted network was associated with lower levels of social support. Network type interacted with partner status: having a partner buffered the negative impact of having a restricted network on social support. Although restricted networks are common among older immigrants, they do not necessarily result in compromised social support. While we may see differences across countries regarding the impact of specific upstream and downstream influences, our findings highlight that both contextual and individual-level resources need to be considered alongside network structure to promote social integration of immigrants as they age.
Keywords: older immigrants; individualism-collectivism; social networks; marital status; social support